Narasi Kehidupan di balik Topeng Tunanetra - Adek Dimas Ajisaka (Institut Seni Indonesia Yogyakarta, 2015)
The Narration of Life behind the Blind Mask. Persons who are blind is the subject that inspires, and motivates the circumstance. The existence of the visually impaired persons indirectly also be social criticism against the life of the community. The limitation has led private owned blind on the value of life and humanity that we appreciate it much more. Introductions and proximity to the persons who are blind raises the creative impulse to embody the values of life and humanity of the blind in the form of works of art. The blind presents in the form of works of art is not merely a display of artistic value but also as an effort to build a positive mentality and thinking through the concepts presented. Blind was involved directly in the process of creation of the work. Facilitating the blind became a print model in the mask. The face mask was chosen because the face is the first individual identity markers and personal representation of the subject. The face became a symbol of insurer liability for what the whole body. The mask being representative of the individual where it has the power to convey the story, experience the value of life and humanity over individual timesKeywords: narration, mask, blind.